Chinook jargon [electronic resource]. - Old employee, formerly of the Hudson Bay Company. ([S.l. : s.n.)
Cover title: Facsimile of the Chinook jargon as used by the Hudson Bay Company and all the Indian tribes and early settlers of the Pacific Northwest / comp. by an old employee, formerly of the Hudson Bay Company--National Union Catalog pre-1956 imprints. Caption title. Electronic reproduction. Mode of access: Internet. 44